Teaching Verb Through TPR Method to EFL Young Leraners at SDN 232Inpres Dulang - Roni La'biran (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
This research is a kind of quantitative method where the writer used experimental. The experiment was held through pre-test and post-test by written test. In this research the writer used total sampling, where all the fourth grade students as population that consist of 19 students being as sample in this research. The result of this research showed that the mean score in pre-test was 28.16 and post-test was 63.58. It showed that the mean score in post-test was higher than pre-test. It means that there was significant improvement of the student knowledge in learning action verbs by using Total Physical Response after giving treatment. The significant was a proved by the data analysis of t-test (9.073) is higher than t-table (2.100), it means that H0 is refused and H1 is accepted. The writer concluded that Total Physical Response is affective in teaching action verbs to EFL young learners at SDN 232 Inpres Dulang and the students were more attention to the teacher’s explanation than teaching action verbs without Total Physical Response.